2003
DOI: 10.1081/ada-120020519
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Treatments for Dual Diagnosis: Twelve-Step and Self-Management and Recovery Training

Abstract: The purpose of this study was to compare the effectiveness of 12-step and cognitive-behavioral (Self-Management and Recovery Training [SMART]) approaches for persons with a dual diagnosis of serious mental illness and substance use disorder in an intensive outpatient/partial hospitalization setting. Participants (n = 112) were alternately assigned to the two treatment conditions, with 50 participants completing the 6-month treatment program. Assessments occurred at baseline, 3 months, and 6 months during treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
81
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 35 publications
1
81
0
1
Order By: Relevance
“…Our findings regarding the absence of effects of substance abuse/dependence on vocational outcomes were not surprising, given that prior studies of individuals receiving return-to-work services reached similar conclusions [16][17][18][19]. In a logistic regression analysis of data from 275 individuals with psychiatric disabilities in three vocational rehabilitation programs, Rogers et al found that current substance abuse did not predict employment status at 3, 6, or 12 months after program entry [19].…”
Section: Implications Of Study Findingsmentioning
confidence: 85%
See 1 more Smart Citation
“…Our findings regarding the absence of effects of substance abuse/dependence on vocational outcomes were not surprising, given that prior studies of individuals receiving return-to-work services reached similar conclusions [16][17][18][19]. In a logistic regression analysis of data from 275 individuals with psychiatric disabilities in three vocational rehabilitation programs, Rogers et al found that current substance abuse did not predict employment status at 3, 6, or 12 months after program entry [19].…”
Section: Implications Of Study Findingsmentioning
confidence: 85%
“…However, findings are also inconsistent regarding the relationship of substance use to employment outcomes in this population [11][12]. While some studies suggest that substance use has deleterious effects on employment outcomes [13][14][15], others have found that clients with this comorbidity do as well as or better in vocational programs than those without comorbidity [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 12-step-oriented drug counseling appears to be as effective as cognitive therapy and supportive expressive therapy in reducing cocaine use (Crits-Cristoph et al, 1999). In addition, TSF and 12-step recovery support do as well in preventing patients' relapse to alcohol and drug use as does CB relapse prevention (Brooks and Penn, 2003;Brown et al, 2002;Wells et al, 1994). …”
Section: Rationale and Effectivenessmentioning
confidence: 99%
“…Although specialized 12 step facilitation (TSF) models for persons with co-occurring disorders have been developed and are valuable (Bogenschutz, 2005;Brooks and Penn, 2003), these are professionally-led therapies designed to prepare patients for peer-led dual focus 12 step groups. The research summarized in this paper is the first study of the effectiveness of participation in a specialized dual focus 12 step fellowship, including an examination of the mechanisms of attitudinal and behavioral change in such groups.…”
Section: "Traditional" Mutual Aid and Dually Diagnosed Personsmentioning
confidence: 99%